2006
DOI: 10.1210/jc.2006-0195
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acids Are Independently Associated with All-Cause and Cardiovascular Mortality in Subjects with Coronary Artery Disease

Abstract: FFA levels independently predict all-cause and cardiovascular mortality in subjects with angiographic CAD. A possible diagnostic use of FFAs warrants further studies, but our results may underline the importance of therapeutic approaches to influence FFA metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(132 citation statements)
references
References 38 publications
6
120
0
6
Order By: Relevance
“…16,17 The significant reduction in the plasma FFA concentration by BREE supplementation, partly, corresponded with previous studies that the BREE supplement significantly reduced total-C and FFA concentrations in the db/db mice. 8 …”
Section: Discussionsupporting
confidence: 86%
“…16,17 The significant reduction in the plasma FFA concentration by BREE supplementation, partly, corresponded with previous studies that the BREE supplement significantly reduced total-C and FFA concentrations in the db/db mice. 8 …”
Section: Discussionsupporting
confidence: 86%
“…However, there are several plausible mechanisms by which FFA might cause CV disease and death [65][66][67][68][69][70][71]. Furthermore, an increase in plasma FFA leads to endothelial activation, inflammation and thrombosis which may initiate early vascular abnormalities that promote atherosclerosis [72][73][74][75][76][77].…”
Section: Hypertriglyceridemia As a Major Component Of Atherogenic Dysmentioning
confidence: 99%
“…Increased plasma FFA concentrations cause endothelial dysfunction, 4 insulin resistance, 5 and endothelial apoptosis. 6 These observations, together with results from epidemiological studies, 7,8 suggest that FFA is involved in atherosclerosis in subjects with insulin resistance. Recently, we have found that FFA-induced endothelial dysfunction is prevented by the inhibition of the renin-angiotensin (Ang) system (RAS) in humans, 9 suggesting that RAS activation by FFA may predominantly contribute to FFA-induced endothelial dysfunction.…”
mentioning
confidence: 95%